Effect of head up tilt on tumor perfusion in a pre-clinical model of prostate cancer - Rand, Taylor Ann (Kansas State University, 2018)
Introduction: Prostate tumor arterioles lack functional smooth muscle and have a diminished myogenic response. Previous research has demonstrated an enhanced prostate tumor blood flow and oxygenation associated with the augmented mean arterial pressure during exercise. Thus, we tested the hypothesis that elevations in the heart-to-prostate tumor hydrostatic gradient via adoption of the 70˚ head-up tilt (HUT) body position would enhance perfusion of the prostate tumor, which may improve tumor oxygenation and radiation therapy outcomes (Study I). Based upon those findings, we performed a secondary analysis (Study II) on previously published prostate hemodynamic responses to an identical tilt-test between young and aged animals. Methods: Study I: Dunning Cell AT-1 tumor cells (100,000) were injected into the ventral lobe of the prostate in male Copenhagen rats (4 mo.; n = 7). Four to six weeks after injection blood flow to the prostate tumor, kidneys, and soleus muscle was measured via the fluorescent microsphere technique in the supine and HUT position. Study II: A secondary analysis was performed on blood flow to the prostate (host tissue of the tumor) in young (6 mo.; n =9) and aged (24 mo.; n=7) male Fisher 344 rats from Ramsey et al., 2007 (39) to determine potential age-associated differences in conductance to this tissue. Results: Study I: No significant difference was observed in blood pressure between the two body positions. Compared to the supine posture, there was a significant reduction in blood flow to the soleus muscle. There was no difference in prostate tumor blood flow or vascular conductance between the supine and HUT position. Study II: In response to tilt, there was a significant reduction in prostate vascular conductance in young rats versus that in the supine posture (P<0.05). In the aged animals, there was no difference in prostate vascular conductance with tilt. Discussion: Contrary to our hypothesis, we did not see any significant differences in either blood flow or vascular conductance to the prostate tumor with manipulations in body position. Importantly, we believe this may be an age-associated effect. Given tumors both co-opt existing arterioles from the host tissue that retain vasomotor control and develop new vessels that lack functional smooth muscle, the enhanced vascular resistance in the prostate with young animals during tilt likely contributed to the lack of change in tumor perfusion with body position given the rats from study I were also young. Given the lack of change in vascular conductance in the prostate with tilt in aged animals, future studies should be performed in aged models of prostate cancer, of which currently there are no immunocompetent aged rodent models of prostate cancer.
Keywords: Prostate Cancer Tumor Perfusion